2013
DOI: 10.1021/ac4018742
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Correlation Spectroscopy: A Method for Determining Surface Binding Kinetics and Thermodynamics

Abstract: These studies describe the implementation of second harmonic correlation spectroscopy (SHCS) to measure the adsorption and desorption kinetics of molecular species associated with a surface. Specifically, the local fluctuations of the measured second harmonic (SH) signal were used to determine the binding kinetics and thermodynamics of (S)-(+)-1,1'-bi-2-napthol SBN intercalation into a 1,2-dioleoyl-sn-glycero-3-phosphocoline (DOPC) bilayer. In order to determine the adsorption and desorption rates, the SH sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“… 29 In the same study, correlation data of a pure DOPC bilayer without addition of any SBN was also investigated and displayed no correlated events, further demonstrating the absence of correlated proportional noise or correlated noise from the bilayer. 29 …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“… 29 In the same study, correlation data of a pure DOPC bilayer without addition of any SBN was also investigated and displayed no correlated events, further demonstrating the absence of correlated proportional noise or correlated noise from the bilayer. 29 …”
Section: Resultsmentioning
confidence: 91%
“…30 − 32 The surface specificity of SHCS eliminates the contributions from diffusion of molecules in solution, such that the only contributing factors to the correlated fluctuations in the SH signal are from the surface binding kinetics. 29 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17, both the adsorption and desorption rate can be retrieved from the measured fluctuations in SH intensity for a single analyte concentration; however, to improve the error of the fitting parameters (N s , k on , and k off ) a separate measurement of the desorption rate can be beneficial, but not wholly necessary. 20,21 When the mechanism of binding does not change with concentration, collecting correlation data from multiple bulk concentrations can also provide the adsorption and desorption rates with increased confidence and reduced error. Monovalent binding, such as SBN intercalating into a DOPC bilayer, generally does not show concentration dependent binding kinetics and is an excellent system to globally fit correlation data to determine both the adsorption and desorption rates of binding.…”
Section: Correlation Function For Surface Binding Kineticsmentioning
confidence: 99%
“…In particular, second harmonic correlation spectroscopy (SHCS) has been used to determine the diffusion coefficient of dye aggregates 17 and long chain para substituted aromatic amphiphiles at a surface. 19 The authors have previously demonstrated the ability of SHCS to determine the binding kinetics of a monovalent interaction between the small molecule ( s )–(+)–1,1’-bi-2-naphthol (SBN) and a 1,2-dioleoyl- sn -glycero-3-phosphocoline (DOPC) lipid bilayer 20 and the more complex interaction between the multivalent proteins cholera toxin b subunit (CTb) and peanut agglutinin (PnA) with monosialotetrahexosylganglioside (GM 1 ) doped DOPC bilayers. 21 These previous studies also illustrate the shortcomings of obtaining surface binding kinetics through traditional adsorption isotherms combined with desorption experiments.…”
Section: Introductionmentioning
confidence: 99%